Bullying in schoolchildren according to Angle's classifications of malocclusion - Ximena Quito-Rabanal; Marcos J. Carruitero (Universidad de Concepción., 2018)
Objective: To compare bullying in schoolchildren according diffe-rent types of Angle's malocclusion. Materials and methods: A cross-sectional and prospective study was performed. 217 schoolchildren were evaluated. A scale-adapted validated questionnaire was applied to measure general bullying. Malocclusion was classified according to Angle's classification. Comparison in bullying between different types of malocclusions was performed by Kruskal Wallis non-parametric test. Multiple linear regression analysis was also performed. Results: No statistically significant differences in bullying between the different types of Angle's malocclusion was found (p=0.295). Multiple linear regression applied to bullying scores treated as dependent variable with malocclusion, sex, and age showed no influence of these variables on bullying (R2=0.0027, p>0.05). Conclusion: Bullying in schoolchildren does not differ according Angle's classification of malocclusion. Further studies are necessary to emphasize the assessment of bullying related to malocclusion of anterior teeth.